2004
DOI: 10.1111/j.0031-9317.2004.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of roots of cucumber (Cucumis sativus) to low temperature severely reduces root pressure, hydraulic conductivity and active transport of nutrients

Abstract: When root temperature dropped below 25 degrees C, there was a sharp drop in the root pressure (P(r)) and hydraulic conductivity of excised roots (Lp(r)) of young cucumber (Cucumis sativus L.) seedlings as measured with the root pressure probe. A detailed analysis of root hydraulics provided evidence for a larger reduction in the osmotic component of Lp(r) (77%) in comparison with the hydrostatic component (34%) in response to the exposure of the root system to 13 degrees C. The activity of the plasma membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 36 publications
3
62
1
2
Order By: Relevance
“…Lee et al (2004) measured positive root pressure in cucumber plants. To test this possibility, we relied on the fact that root pressure rapidly declines when roots are chilled (Lee et al, 2004), whereas cold inhibition of phloem transport is a localized phenomenon (Webb, 1967). Therefore, root chilling should inhibit xylem water flux, but not sap movement through sieve tubes, in the aerial portion of the plant.…”
Section: Water From the Xylemmentioning
confidence: 99%
“…Lee et al (2004) measured positive root pressure in cucumber plants. To test this possibility, we relied on the fact that root pressure rapidly declines when roots are chilled (Lee et al, 2004), whereas cold inhibition of phloem transport is a localized phenomenon (Webb, 1967). Therefore, root chilling should inhibit xylem water flux, but not sap movement through sieve tubes, in the aerial portion of the plant.…”
Section: Water From the Xylemmentioning
confidence: 99%
“…Lee et al (2004) reported root pressure, hydraulic conductivity and nutrients active transport were seriously reduced when roots were exposed to low temperature. So, nutrient uptake could be inhibited by low RZT (Peng and Dang 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have emphasized the changes in water relations because water homeostasis is essential for plant survival under this stress condition, and a significant symptom of chilling injury is shoot water deficit resulting from imbalance between water transport and transpiration [2]. It has been well documented that root water transport is sharply suppressed by exposure to low temperature in a number of species, including maize [3][4][5][6], rice [7], bean [8], spinach [9], aspen [10], cucumber and figleaf gourd [11,12]. Some studies have also demonstrated that a decrease in transpiration follows the reduction in root water flow [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Techniques used were Northern blot, semi-quantitative reverse transcription (RT)-PCR and real-time RT-PCR using SYBR green dye in species such as Arabidopsis [20], maize [6] and rice [7]. Comparative analysis between cucumber (chilling sensitive) and figleaf gourd (chilling resistant) indicated that the decrease in cell hydraulic conductivity (Lp) at low temperature was associated with the open/close state of water channels [11,12]. However, in chilling-sensitive maize, the decrease in root Lp upon chilling was due to oxidative damage to the membranes rather than a decrease in aquaporin amount or a change in phosphorylation status [6].…”
Section: Introductionmentioning
confidence: 99%